Salinibacter Sensory Rhodopsin: SENSORY RHODOPSIN I-LIKE PROTEIN FROM A EUBACTERIUM - Kitajima-Ihara, Tomomi (American Society for Biochemistry and Molecular Biology, 2008)
Halobacterium salinarum sensory rhodopsin I (HsSRI), a dual receptor regulating both negative and positive phototaxis in haloarchaea, transmits light signals through changes in protein-protein interactions with its transducer, halobacterial transducer protein I (HtrI). Haloarchaea also have another sensor pigment, sensory rhodopsin II (SRII), which functions as a receptor regulating negative phototaxis. Compared with HsSRI, the signal relay mechanism of SRII is well characterized because SRII from Natronomonus pharaonis (NpSRII) is much more stable than HsSRI and HsSRII, especially in dilute salt solutions and is much more resistant to detergents. Two genes encoding SRI homologs were identified from the genome sequence of the eubacterium Salinibacter ruber. Those sequences are distantly related to HsSRI (∼40% identity) and contain most of the amino acid residues identified as necessary for its function. To determine whether those genes encode functional protein(s), we cloned and expressed them in Escherichia coli. One of them (SrSRI) was expressed well as a recombinant protein having all-trans retinal as a chromophore. UV-Vis, low-temperature UV-Vis, pH-titration, and flash photolysis experiments revealed that the photochemical properties of SrSRI are similar to those of HsSRI. In addition to the expression system, the high stability of SrSRI makes it possible to prepare large amounts of protein and enables studies of mutant proteins that will allow new approaches to investigate the photosignaling process of SRI-HtrI.